Evaluasi Adaptasi Arsitektur terhadap Pandemi Covid-19 pada Bangunan Fasilitas Kesehatan di Makassar - Khilda Wildana Nur; Andi Annisa Amalia; Siti Fuadillah Alhumairah Amin (Universitas Sebelas Maret Surakarta, 2022)
Architecture responds to the Pandemic with a unified and massive form, while the Covid-19 demands buildings that are completely void. This research was conducted at the healthcare facility building at Khadijah Hospital in Makassar which is expected to be a representative building for mapping the transmission of Covid-19 in public facilities. This study aims to examine adaptation strategies from the architectural realm in healthcare facilities combined with studies on COVID-19 mitigation and Muhammadiyah mediation in applying Islamic concepts. This research is descriptive exploratory to the object of research. The data collection method was obtained from the results of observations, interviews, and literature studies which were then analyzed using synchronic reading and diachronic reading methods, aligning all available information so that conclusions were obtained from all references. This study results that adaptation is more likely to regulate circulation, limit the number of people, and reduce furniture. Providing additional rooms such as green open spaces, and special cabin for patients and visitors are not fully accommodated because health care facility considers the cost and construction time. Another result is that the form of architectural adaptation raises the potential for design based on natural interventions such as the healing environment approach and biophilic design.